Bovine‐derived xenograft in combination with autogenous bone chips versus xenograft alone for the augmentation of bony dehiscences around oral implants: A randomized, controlled, split‐mouth clinical trial. (5th November 2019) - Temmerman, Andy; Cortellini, Simone; Van Dessel, Jeroen; De Greef, Alexander; Jacobs, Reinhilde; Dhondt, Rutger; Teughels, Wim; Quirynen, Marc
Abstract: Aim: The aim of the study was to evaluate whether the use of a xenograft is not inferior to the use of xenograft and autogenous bone chips in treating dehiscences at implant placement. Materials and Methods: After implant placement, leaving a dehiscence, control sites were treated using a composite graft (autogenous bone chips and xenograft) and at the test sites 100% xenograft was used. Both sites were covered with a resorbable collagen membrane. Dehiscences were measured clinically at implant placement and at re‐entry. CBCT was taken immediately after implant placement and after 4 months. Results: In total, 28 GBR procedures were performed in 14 patients. On average, the change in vertical defect height was 2.07 mm (46.7%—test group) and 2.28 mm (50.9%—control group) ( p  > .05). The horizontal defect width at the implant shoulder change on average 1.85 mm (40.5%—test group) and 1.75 mm (40.9%—control group) ( p  > .05). On average, a loss in augmentation thickness of 0.45 mm (68.9%—test group) and 0.64 mm (55.5% control group) between implant placement and augmentation and abutment surgery was obtained at the implant shoulder. Conclusion: Both treatment modalities seem to work to a certain extent. At implant shoulder level, the augmentation thickness seems to be disappeared after the healing phase. (NCT03946020).